Misspecification Testing: Non-Invariance of Expectations Models of Inflation - Castle, J; Doornik, J; Hendry, D; Nymoen, R (Taylor and Francis, 2014)
Many economic models (such as the new-Keynesian Phillips curve, NKPC) include expected future values, often estimated after replacing the expected value by the actual future outcome, using Instrumental Variables (IV) or Generalized Method of Moments (GMM). Although crises, breaks, and regime shifts are relatively common, the underlying theory does not allow for their occurrence. We show the consequences for such models of breaks in data processes, and propose an impulse-indicator saturation test of such specifications, applied to USA and Euro-area NKPCs.